Revising women : eighteenth-century "women's fiction" and social engagement - Backscheider, Paula R. (Johns Hopkins University Press, 2000)
"Revising Women is a collection of essays by a distinguished group of feminist critics. Each essay is a contribution to the history of the English novel and demonstrates the "reactivation" of texts, a kind of criticism that produces rich contextualization in order to reveal the story beneath - not only of the individual writer but also of a text that is a cultural production with the potential to reveal why we and our society are as we are. Developing ways of using history in relation to literature, each essay takes up large historical events and issues, and interprets in fine detail what individuals do with them."